c) (xy-y)(3xy+5x) dla x=2, y=1
(xy-y)(3xy+5x)=[tex]3x^{2} y^{2}+ 5x^{2}y- 3xy^{2} -5xy[/tex]
po podstawieniu:
[tex]3*2^{2}*1^{2}+5* 2^{2}*1-3*2*1^{2} -5*2*1 =3*4+5*4-3*2-5*2=12+20-6-10=32-16=16[/tex]
d) (a+4b) - (5+2a) - (3b-5), a= -1, b=1
(a+4b) - (5+2a) - (3b-5) = a + 4b - 5 - 2a - 3b + 5 = -a + b
po podstawieniu:
-(-1)+1=1+1=2
e) [tex]-\frac{1}{2} a^{3}b+ \frac{2}{3}ab+ \frac{1}{2} a^{3}b +\frac{1}{3}ab[/tex] dla a=1/3, b=9
redukcja wyrazów podobnych - wyrazy z [tex]a^{3}b[/tex] się ze sobą skracają (bo 1/2+(-1/2)
2/3ab+1/3ab = ab
po podstawieniu
1/3*9 = 3